Treatment results in patients with acute limb ischemia - V. A. Gubka; I. A. Konovalenko; O. V. Suzdalenko (Zaporozhye State Medical University, 2018)
Aim. Acute limb ischemia (ALI) is one of the most serious subjects for life quality declining and often results in patients' disability. The incidence of ALI increases from year to year and currently counts about 50 to 100 cases per 100 000 persons in EU and USA. Methods and results. 188 cases were studied, 61% male, 39% female. The average age was 66,8±4,2 years. Among clinical events that caused ALI were atherothrombosis in 90 (47,87%) patients, embolisms in 92 (48,94%) cases, acute thrombosis of bypass graft in 6 (3,19%) patients. Conclusion. Limb salvage rate in patients after complex revascularization surgery was 100%. Thus we can state, that thrombectomy with following one stage angioplasty or bypass grafting improves clinical outcomes and limb salvation rate in patients with ALI.